(untitled) (Altre Modernità, 2016)
The debate on novelties within the social movements examines the theories built underneath, as well as its composition, accounts, itineraries and sets of protest, that is, it also covers the practical dimensions of the references. In this theory-practice game, the agro-ecological social movement is a reference, among others, which empowers to discuss, to examine and to question the relationship of subordination that have existed between these two fields (theory and practice). What is new here is, if one can say so, to reproduce an exercise in order to reverse the link relationship and raise questions and creative spaces starting from the practice. This implies a series of epistemological considerations aiming to recreate a space of political production from the bottom, by transforming the conventional logic of universalism into a pluriversalism based logic. Within it, there is the quest for a new epistemological reference and situated knowledge construction where the social subject is the main focus of the created scenary. According to this relationship, the agro-ecological movement is examined as a holder of experiences and practices which allow to build link relationships between a theory under permanent construction and a practice based on the creative externality of the subjects in action.